Immigration or emigration country? Migration trends and their socio-economic background in Hungary: A longer-term historical perspective. - Ireń God̈ri; Beĺa Solteśz; Boroḱa Bodacz-Nagy (Hungarian Demographic Research Institute, 2014)
This paper - elaborated in the framework of the international SEEMIG project - aims to analyse specific development paths as regards migratory, labour market, human capital and demographic processes and patterns in Hungary. The objective is to offer a review of migration processes, labour market characteristics, demographic and human capital development, and at the same time highlighting inter-linkages between these different factors. The analysis spans two sections of the period examined: it offers a concise historical review of the changes in these processes from the 1950s to the present day, and it then examines in detail the current situation and the changes in the recent past, including causes and consequences, with a particular focus on the past decade.
Keywords: J61; 300; Fertilität; Weibliche Arbeitskräfte; Arbeitsmarkt; Ungarn